Community and Health Care Provider Preferences for Bacterial Sexually Transmitted Infection Testing Interventions for Gay, Bisexual, and Other Men Who Have Sex With Men: e-Delphi Study - Anna Yeung; Ryan Lisk; Jayoti Rana; Charlie B Guiang; Jean Bacon; Jason Brunetta; Mark Gilbert; Dionne Gesink; Ramandip Grewal; Michael Kwag; Carmen H Logie; Leo Mitterni; et al. (JMIR Publications, 2023)
BackgroundCanadian clinical guidelines recommend at least annual and up to quarterly bacterial sexually transmitted infection (STI) testing among sexually active gay, bisexual, and other men who have sex with men (GBM). However, testing rates are suboptimal. Innovative solutions are needed to close the gap because there is currently limited knowledge on how best to approach this issue. ObjectiveOur aim was to build consensus regarding interventions with the greatest potential for improving local STI testing services for GBM communities in Toronto, Ontario, Canada, using a web-based e-Delphi process. MethodsThe e-Delphi method involves using a panel format to conduct successive rounds of prioritization, with feedback between rounds, to determine priorities among groups. We recruited experts separately from the community (GBM who sought or underwent STI testing in the preceding 18 months; conducted between October 2019 and November 2019) and health care providers (those who offered STI testing to GBM in the past 12 months; conducted between February 2020 and May 2020). The experts prioritized 6 to 8 potential interventions on a 7-point Likert scale ranging from definitely not a priority to definitely a priority over 3 survey rounds and ranked their top 3 interventions. Consensus was defined as ≥60% within a ±1 response point. Summaries of responses were provided in successive rounds. We reported the percentage of a priority (encompassing somewhat a priority, a priority, and definitely a priority responses) at the end of the final round of the survey. ResultsOf the community experts (CEs), 84% (43/51) completed all rounds; 19% (8/43) were living with HIV; 37% (16/43) were HIV negative and on pre-exposure prophylaxis; and 42% (18/43) were HIV negative and not on pre-exposure prophylaxis. We reached consensus on 6 interventions: client reminders (41/43, 95%), express testing (38/43, 88%), routine testing (36/43, 84%), an online booking app (36/43, 84%), online-based testing (33/43, 77%), and nurse-led testing (31/43, 72%). The CEs favored convenient interventions that also maintain a relationship with their provider. Of the provider experts (PEs), 77% (37/48) completed all rounds; 59% (22/37) were physicians. Consensus was reached on the same 6 interventions (range 25/37, 68%, to 39/39, 100%) but not for provider alerts (7/37, 19%) and provider audit and feedback (6/37, 16%). Express testing, online-based testing, and nurse-led testing were prioritized by >95% (>37/39) of the PEs by the end of round 2 because of streamlined processes and decreased need to see a provider. ConclusionsBoth panels were enthusiastic about innovations that make STI testing more efficient, with express testing rating highly in both the prioritizations and top 3 rankings. However, CEs preferred convenient interventions that involved their provider, whereas PEs favored interventions that prioritized patient independence and reduced patient-provider time. International Registered Report Identifier (IRRID)RR2-10.2196/13801